Highly Pathogenic Avian Influenza A(H5N1) Virus Clade 2.3.4.4b in Wild Birds and Live Bird Markets, Egypt - Rabeh El-Shesheny; Yassmin Moatasim; Sara H. Mahmoud; Yi Song; Ahmed El Taweel; Mokhtar Gomaa; Mina Nabil Kamel; Mohamed El Sayes; Ahmed Kandeil; Tommy T. Y. Lam; Pamela P. McKenzie; Richard J. Webby; et al. (Pathogens, 2022)
Clade 2.3.4.4 H5Nx influenza viruses have further diversified into several subclades. Sub-clade 2.3.4.4b H5N1 viruses have been widely circulating in wild birds and detected in Europe, Africa, Asia, and North America since October 2020. In this study, we report the first detection of highly pathogenic avian influenza H5N1 clade 2.3.4.4b viruses in wild birds and domestic ducks from live bird markets in Egypt. Phylogenetic analysis revealed that the Egyptian H5N1 virus retained the genomic composition of Eurasian strains. Mutations in the viral proteins associated with zoonotic potential and pathogenicity were detected in Egyptian isolates. Egypt is considered a hot spot for the evolution of the influenza virus, so active surveillance of avian influenza viruses in Egypt is warranted.